In Vitro Apoptotic Cell Death Assessment - Pereira, Lilian Cristina [UNESP]; de Souza, Alecsandra Oliveira; Miranda, Raul Ghiraldelli; Dorta, Daniel Junqueira [UNESP] (Springer Nature, 2021)
Chemical compounds induce cytotoxicity by various mechanisms, including interference in membrane integrity, metabolism, cellular component degradation or release, and cell division. Between the classic death pathways, namely, autophagy, apoptosis, and necrosis, apoptosis have been in the focus for the last several years as an important pathway for the toxicity of different types of xenobiotics. Because of that, having the tools to evaluate it is key for understanding and explaining the toxicodynamics of different classes of substances. Here, we describe a wide array of classic assays that can be easily implemented to evaluate apoptosis induction.
Keywords: Annexin-V; Apoptosis; Cell death; Nuclear fragmentation; Phosphatidilserine exposure